Determinan Keputusan Pembelian Secara Online: Studi Kasus Pada Konsumen Belanja Online Di Desa Setupatok Kecamatan Mundu Cirebon - Suci Diani; Yopi Nisa Febianti; Ratna Tiharita (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
This study aims to describe (1) how people consider the price factor, (2) the ease factor, and (3) the trust factor in making online purchasing decisions. The purpose of this study is to find out how people consider the price factor, the ease factor, and the trust factor in making online purchasing decisions. This research was conducted in Setupatok Village, Mundu District, Cirebon Regency. This research uses descriptive qualitative method. Data collection techniques used, namely interviews, observation, and documentation. Data analysis was carried out using qualitative data analysis, namely data collection, data reduction, data presentation, and conclusion/verification. Meanwhile, the validity of the data was tested by technical triangulation. The results of the study show: (1) on the price factor, consumers tend to choose products that have affordable prices. The way to do this is by comparing the prices of one store with another and choosing to buy on discount products or when there are certain events such as HARBOLNAS (Hari Belanja Online Nasional), (2) then on the ease factor, consumers tend to choose online that provide a system COD (Cash On Delivery), especially for novice consumers, and (3) On the trust factor, consumers trust online that have a good reputation.